Effect of Depth on Folding Type Ground Anchor Tensile Force in Soft Soil - Muhammad Idhil Maming; Abdul Rachman Djamaluddin; Ariningsih Suprapti; Muhammad Ilham Akbar Mallombasang (Lowland Technology International, 2022)
Soft soil is one type of soil that is commonly found in Indonesia, but in construction, this type of soil is often a problem, namely for soil stability in the process of making building structures. In an effort to determine the stability of the soil or slope, an anchor is used as a measuring medium. Several structures have used anchors and have been developed for various purposes such as slope reinforcement, retaining walls, tunnel stability, and so on. This research aims to analyse the effect of the depth of folding type soil anchor on the tensile force and to analyse the comparison of the tensile force of laboratory experimental testing results with full-scale field testing. The research method was carried out by testing the tensile force of laboratory-scale folding type anchors with depths of 30cm, 60cm and 90cm and field-scale tests using folding type anchors with depths of 100cm, 200cm and 300cm. From the results of tests that have been carried out in the laboratory and the field, it can be concluded that the folding type model anchor does not need to be designed too deep because the anchor has a critical limit where even though the depth is increased it no longer adds a greater maximum tensile force. In addition, the comparison of the tensile force of the laboratory experimental test results with the field full-scale testing.resulted in similar properties of the maximum tensile test results.